Shared responsibility for decision-making in NICU: A scoping review - Pellikka Hanna-Kaisa; Axelin Anna; Sankilampi Ulla; Kangasniemi Mari (SAGE Publications Ltd, 2025)
Background: Shared responsibility is an essential part of family-centred care and it characterizes the relationship between parents and healthcare professionals. Despite this, little is known about their shared responsibility for decision-making in neonatal intensive care units.
Aim: The aim of this scoping review was to identify previous studies on the subject and to summarize the knowledge that has been published so far.
Method: The review was conducted using electronic searches in the CINAHL, PubMed, Scopus and PsycINFO databases and manual searches of the reference lists of the selected papers. The searches were limited to peer-reviewed papers that had been published in English from 2010 to September 2021. The data were selected based on inclusion and exclusion criteria and the findings were inductively summarized. We identified eight papers that met the inclusion criteria.
Ethical considerations: The scoping review was conducted according to good scientific practice by respecting authorship and reporting the study processes accurately, honestly and transparently.
Results: The results showed that shared responsibility for decision-making was based on the parents’ intentions, but the degree to which they were willing to take responsibility varied. The facilitating and inhibiting factors for shared responsibility for decision-making were related to the communication between parents and professionals. The impact was related to the parents’ emotions.
Conclusion: It is essential that parents and professionals negotiate how both parties will contribute to their shared responsibility for decision-making. This will enable them to reach a mutual understanding of what is in the infants’ best interests and to mitigate the emotional burden of decisions in neonatal intensive care units. More research is needed to clarify the concept of shared responsibility for decision-making in this intensive care context.